"What makes me click?" The effects of images and color in consumer-based pandemic health messages. Issue 2 (3rd April 2023) - Chowdhury, Tilottama G.; Norberg, Patricia; Asare, Anthony K.; Kang, Jun; Bannor, Richard
ABSTRACT: Health messaging for diseases has been an important research area in marketing. The objectives of this research are to explore response to health communications for highly threatening pandemics. We demonstrate that, in addition to message framing, imagery and text color affect intentions to respond to pandemic messages. We find that social imagery combined with positive framing increases intentions to respond, and that text in blue further increases response to messages. These results suggest that text color and social imagery matter when attempting to engage consumers in health messages about highly threatening diseases.